2016
DOI: 10.1038/srep38509
|View full text |Cite
|
Sign up to set email alerts
|

A Very Stable High Throughput Taylor Cone-jet in Electrohydrodynamics

Abstract: A stable capillary liquid jet formed by an electric field is an important physical phenomenon for formation of controllable small droplets, power generation and chemical reactions, printing and patterning, and chemical-biological investigations. In electrohydrodynamics, the well-known Taylor cone-jet has a stability margin within a certain range of the liquid flow rate (Q) and the applied voltage (V). Here, we introduce a simple mechanism to greatly extend the Taylor cone-jet stability margin and produce a ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 45 publications
1
63
0
Order By: Relevance
“…As the electrical potential difference increases, the viscosity and surface tension of the solution will be overcome. Then, a whipping instability of the jet will occur, causing it to travel in a vigorous spiral motion . Apart from whipping instability, the splaying or splitting of a single solution jet into multifilament can also happen .…”
Section: Introductionmentioning
confidence: 99%
“…As the electrical potential difference increases, the viscosity and surface tension of the solution will be overcome. Then, a whipping instability of the jet will occur, causing it to travel in a vigorous spiral motion . Apart from whipping instability, the splaying or splitting of a single solution jet into multifilament can also happen .…”
Section: Introductionmentioning
confidence: 99%
“…Both configurations have their advantage and disadvantages in different aspects and perspectives. The Taylor cone formation is the most important phenomenon to produce finer and even fiber diameter using the minimum voltage 40,41 . The sphere shaped polymer droplet creation and the uniform Taylor cone formation are the key advantages in needle electrospinning, that facilitates to produce smooth and finer fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Among several methods for mass production of nanofibers, creation of multiple jets using rotating disks 32 , conical wire coil 33 , rollers 34 , balls 14 , bubbles 35 , rod 36 , Twisted wire spinnerets 37 and cones 38,39 have turned the electrospinning technique, the most effective process for nanofiber production. In most of the needleless upward electrospinning, numerous jets are formed simultaneously from the liquid surfaces without the influence of capillary effect, which typically requires a high voltage upto 90 kV to form a Taylor cone and for fiber formation [40][41][42] . A sphere shape profile creation on the electrospinning spinneret can reduce the applied voltage and produce fine fibers with minimum voltage 40 .…”
mentioning
confidence: 99%
“…The existence of the hysteresis phenomena might be connected to the fact that the ratios of the normal and the tangential electric forces are different in the mentioned cases (Morad, et al, 2016).…”
Section: Variable Physical Parametersmentioning
confidence: 99%
“…According to Morad, Rajabi, Razavi, and Pejman Sereshkeh (2016), the stable jet mode can be maintained in a greater voltage range for lower flow rates than for the higher ones because the stability of a stable jet decreases as the flow rate increases. Ku and Kim (2002) found that the standard deviation of the droplet diameter for a highly viscous liquid has a minimal value (i.e.…”
Section: Electrospray Modesmentioning
confidence: 99%